1989
DOI: 10.1148/radiology.173.3.2813792
|View full text |Cite
|
Sign up to set email alerts
|

Optimal needle size for renal biopsy: in vitro and in vivo evaluation.

Abstract: To evaluate the success and complication rates of small (16- and 18- gauge) needles in biopsy of the kidney, the authors performed in vitro biopsy in a cadaveric kidney and in vivo renal biopsy in 141 patients. Best results were obtained with a 16-gauge modified Menghini needle. In vitro, 9.7 +/- 5.7 (mean +/- standard deviation) glomeruli were retrieved, and the average length of tissue cores was 17.8 mm +/- 8.2. In vivo, 10.63 +/- 6.64 intact glomeruli were retrieved, and a definitive histologic diagnosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
4

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 0 publications
0
17
0
4
Order By: Relevance
“…However, these scores do not correlate with creatinine values and histologic findings. Although focal infarcts are somewhat better delineated with POS than with COl, the conspicuity of biopsy-related AV fistulas on PDS is inferior to that obtained with COL A B Figure 5 Postbtopsy AV fistula demonstroted by PDS (A) and COl (8). Using PDS, renal allogr,lft demonstrates score 0 (cortical bJushl.…”
Section: Resultsmentioning
confidence: 96%
“…However, these scores do not correlate with creatinine values and histologic findings. Although focal infarcts are somewhat better delineated with POS than with COl, the conspicuity of biopsy-related AV fistulas on PDS is inferior to that obtained with COL A B Figure 5 Postbtopsy AV fistula demonstroted by PDS (A) and COl (8). Using PDS, renal allogr,lft demonstrates score 0 (cortical bJushl.…”
Section: Resultsmentioning
confidence: 96%
“…However, the present study demonstrated that there still remain several points to be further improved. 8,9 In 394 renal biopsies, 10 patients (2.5%) needed an extended rest period in bed. Macrohematuria, which occurred in 29 patients (7.4%), was transient (5.8%) or long-lasting (1.5%).…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of controversy exists concerning the size of the needle that should be used for renal biopsy (3,8,11,13,15,17,20,21,25,(29)(30)(31)(32)35). To our knowledge no comparative studies of the Biopty Instrument dealing with the use of 1.2-mm versus 2.0-mm needles in terms of diagnostic yield and rate of complications have been published.…”
Section: Discussionmentioning
confidence: 99%